Ensinar e aprender nos anos iniciais do ensino fundamental: contribuições da teoria histórico-cultural e da teoria do ensino desenvolvimental - Sylvio, Mara Cristina de (2015)
This research, conducted at the line of research Education, Teacher Professionalization and Work Education on the Education Postgraduate Program at the Faculty of Education of the Federal University of Goiás, has as it object, the teaching in the early years of elementary school. The overall goal is to understand and systematize the main contributions of cultural-historical theory of Vygotsky and developmental teaching theory of Davidov for this stage of education, through a bibliographic and documentary research. The theoretical framework consists of the work of Leontiev (1998 and 2006); Vygotsky (1991, 2001a, 2001b, 2010); Davidov (1978, 1988) and Davydov and Markova (1987) and also dissertations, theses, scientific articles and books that present the contributions of historical-cultural theory and the developmental education theory for school education. We had reference to the dialectical materialist method of developing bibliographical and documentary research. In document analysis, we focus on the National Curriculum Guidelines for Elementary Education and the National Curriculum Guidelines for the Pedagogy course. The research allows us to state that the historical-cultural theory and the theory of developmental education is knowledge that can support the teacher's pedagogic practice of the early years in the teaching of elaborate and systematic culture in the form of school subjects, becoming therefore a didactic knowledge of great importance. Both theories share the same premise that access to and appropriation of historically produced culture in the form of school subjects be conducive to human development. The educational process is understood by Davidov as a complex process of teaching and learning in which, to take ownership of human culture, students will develop certain capacities of thought, especially the theoretical thought, which could not be developed otherwise.